2018
DOI: 10.1021/acs.jafc.8b01753
|View full text |Cite
|
Sign up to set email alerts
|

Lauric Acid Accelerates Glycolytic Muscle Fiber Formation through TLR4 Signaling

Abstract: Lauric acid (LA), which is the primary fatty acid in coconut oil, was reported to have many metabolic benefits. TLR4 is a common receptor of lipopolysaccharides and involved mainly in inflammation responses. Here, we focused on the effects of LA on skeletal muscle fiber types and metabolism. We found that 200 μM LA treatment in C2C12 or dietary supplementation of 1% LA increased MHCIIb protein expression and the proportion of type IIb muscle fibers from 0.452 ± 0.0165 to 0.572 ± 0.0153, increasing the mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Very little is known regarding the specific effect of LA in altering metabolic processes in vivo. For example, a 1% LA supplemented diet promoted glycolytic muscle formation in mice [ 26 ]. In another study, LA supplementation of control diet at 1% promoted the lactation function of mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known regarding the specific effect of LA in altering metabolic processes in vivo. For example, a 1% LA supplemented diet promoted glycolytic muscle formation in mice [ 26 ]. In another study, LA supplementation of control diet at 1% promoted the lactation function of mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These effects are consistent with a previous report showing that the expression of both GLUT-4 and CPT-1 are increased in myotubes upon LA treatment [ 41 ]. Further, an LA supplemented diet promoted glycolytic muscle formation in mice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tlr4 was reported previously as involved in inflammatory responses, mainly in the PI3K/AKT 42 and NF-κB signaling pathways. 43 Tlr4 can also act as a negative regulator to inhibit cell proliferation in cutaneous squamous cell carcinoma cells. 44 Tlr4 may have a regulatory role in the growth of cancer cells, but a regulatory role in normal cell growth has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In nutritional factors, capsaicin, apple polyphenols, and carnitine have been reported to influence the skeletal muscle fiber type. , Besides, fatty acids have also been demonstrated to exert physiological and pathophysiological effects on changing skeletal muscle metabolism and function . In the previous studies in our lab, it has been shown that lauric acid can promote the formation of glycolytic fibers …”
Section: Introductionmentioning
confidence: 91%